Proceedings of the 4th Eurographics Workshop on Sketch-Based Interfaces and Modeling 2007
DOI: 10.1145/1384429.1384445
|View full text |Cite
|
Sign up to set email alerts
|

Newton's Pen

Abstract: We present Newton's Pen, a statics tutor implemented on a "pentop computer," a writing instrument with an integrated digitizer and embedded processor. The tutor, intended for undergraduate education, scaffolds students in the construction of free body diagrams and equilibrium equations. This project entailed the development of sketch understanding techniques and user interface principles for creating pedagogically-sound instructional tools for pentop computers. Development on the pentop platform presented nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Many sketch understanding systems exist but most stick to a single domain because they use sketch recognition (Lee et al 2007;de Silva et al 2007;Valentine et al 2012). No other sketch understanding systems use structure mapping as a model for comparison.…”
Section: Related Workmentioning
confidence: 99%
“…Many sketch understanding systems exist but most stick to a single domain because they use sketch recognition (Lee et al 2007;de Silva et al 2007;Valentine et al 2012). No other sketch understanding systems use structure mapping as a model for comparison.…”
Section: Related Workmentioning
confidence: 99%
“…Research from the CSEd community on text-based coding as a strategy [4,8] and findings on intelligent tutoring systems based on handwritten input for education [9,10,11,12] motivate us to explore the following research questions:…”
Section: Introductionmentioning
confidence: 99%
“…Work similar to Le & Nakagawa's research [11], which introduces a system that recognizes online handwritten mathematical expressions (MEs) to assist on K-12. De Silva et al [12] also found tutoring systems useful in contexts such as circuits calculi on Kirchhoff laws.…”
Section: Introductionmentioning
confidence: 99%